Kobieta i mężczyzna kustoszami Ewangelii życia w kontekście społecznego eksperymentu gender - Olczyk, Maciej (Teologia i Moralność, 2018)
The analysis of the mystery of life can be helpful to overcome the current crisis of woman’s and a man’s sexual/gender identity caused by radical theses of the gender ideology. In the light of biblical anthropology we can know better the multidimensional nature of human life. The life-cycle mystery is closely linked with the process of life transmitting. The woman and man have received from God the capability and mission to transmit life. This ability inscribed in the nature of the person expresses the essential feature of their vocation as beings created in the image of God. Woman and man should to be life-giving, as God is the life-giving Creator. The negation of this life-giving aspect of human nature present in the radical theses of gender ideology places this theory in obvious contradiction to the Gospel of life. For this reason the gender ideology can be considered as a serious threat not only to individual man but to all human family.